What can we learn about crisis management in the polycrisis era? Insights from Finland’s international public policy network - Keinänen, Jukka; Halonen, Maija; Luoto, Ilkka (Emerald, 2025)
Purpose This study aims to examine organizational crisis management from a polycrisis perspective. We examine how network governance reacts to multiple simultaneous crises and the lessons learned from these reactions. Design/methodology/approach Our study analyzes interview data gathered from the Team Finland network, which includes public and non-governmental organizations. The network primarily offers internationalization services for small- and medium-sized enterprises. The data were analyzed to better understand the complexities associated with polycrisis and their connection to organizational and regional resilience. Findings We analyzed 28 interviews and public sector administrative documents from which three main categories emerged: (1) awareness of crises, (2) adaptation by reorganization and (3) rethinking regions. The ability to collaboratively navigate the complexities of the polycrisis era was particularly highlighted. Originality/value This study combines themes of polycrisis, network governance and resilience, prioritizing the development of regionally sensitive crisis-response frameworks that integrate public and private sector resources and treat multiple crises as a unified challenge.
Keywords: Polycrisis; Public organization; Network governance; Resilience; Region; Team Finland; crisis management; fi=Aluetiede|en=Regional Studies|